UJI Resonantor BUMBUNG TERTUTUP pada perangkat Gamelan Slentem dan gender UNTUK PENGUATAN BUNYI - Yoyon K. Suprapto1, ; Aditya Prapanca2, (Matematika dan Sains, 2011)
Gamelan@consists of@many devices which has@the characteristics sound. It is in fluenced by@ resonantor on each gamelanfs device. Resonantor@is useful@to strengthen the@sound character resulted by@set of gamelan. Each@gamelanfs device has the resonator in different form. It usually@located@under@the sound-producing@metal. Tubular is one of resonantor@form used@in@slentem@and@gender.@The diameter and length of the resonantor tube enfluenced to @the sound produced@by resonantors. @